Singing the Old Song: The Historical Politics of the Masyumi Party in the 1950s in East Java, Indonesia - Wirayuda, Arya Wanda (Paramita: Historical Studies Journal, 2024)
Masyumi, Indonesia’s first modern Islamic party, introduced new methods of political campaigning in East Java because of its traditional Islamic base. However, this case has not been seriously studied by scholars. Using the historical method, this article aims to explain the historical politics of the Masyumi party, which temporarily saved the party from declining trust and support. In its analysis, this article uses the perspective of past politics. This article shows how the strategy of the Masyumi Party sustained the party’s dream of an ideal Indonesian state. The strategy of the Masyumi Party in East Java, Indonesia, often differed from other provinces because of its historical politics. The party was more interested in attacking the communist groups than other parties. This was because these groups used the issue of Masyumi’s radicalism in rebellions in other regions. As a result, Masyumi was not concerned with other political forces, such as traditional Muslims and their patron-client relationships, and illiterate society. Although the Masyumi Party did not survive, partly because the Communist Party influenced the Indonesian government, the historical politics of this first Islamic party is important for future research in cities or regencies in East Java with a large traditional Islamic base.Masyumi, partai Islam modern pertama di Indonesia, memperkenalkan metode baru dalam kampanye politik di Jawa Timur karena basis Islam tradisionalnya. Namun, hal ini belum banyak dikaji secara serius oleh para akademisi. Dengan menggunakan metode historis, artikel ini bertujuan untuk menjelaskan sejarah politik partai Masyumi yang untuk sementara waktu menyelamatkan partai tersebut dari penurunan kepercayaan dan dukungan. Dalam analisisnya, artikel ini menggunakan perspektif sejarah politik. Artikel ini menunjukkan bagaimana strategi Partai Masyumi mempertahankan mimpi partai tentang negara Indonesia yang ideal. Strategi Partai Masyumi di Jawa Timur, Indonesia, sering kali berbeda dengan provinsi lain karena sejarah politiknya. Partai ini lebih tertarik untuk menyerang kelompok-kelompok komunis daripada partai-partai lain. Hal ini dikarenakan kelompok-kelompok tersebut menggunakan isu radikalisme Masyumi dalam pemberontakan di daerah lain. Akibatnya, Masyumi tidak peduli dengan kekuatan politik lain, seperti Muslim tradisional dan hubungan patron-klien mereka, dan masyarakat yang buta huruf. Meskipun Partai Masyumi tidak bertahan, sebagian karena Partai Komunis mampu mempengaruhi pemerintah Indonesia, sejarah politik partai Islam pertama ini penting untuk penelitian di masa depan di kota-kota atau kabupaten di Jawa Timur yang memiliki basis Islam tradisional yang besar.